Enhanced Cl– electrosorptive performance of activated carbon fibre via modification by TiO2 and polyaniline. Issue 6 (December 2022) - Liang, Meisheng; Liu, Hongyan; Yang, Chao; Chen, Yichen
Abstract: Chloride ions in reclaimed water are the main contributors to corrosion of pipelines. In this study, titanium dioxide (TiO2 )-and polyaniline (PANI)-modified activated carbon fibre (ACF) electrodes were prepared using the sol–gel method and in situ polymerisation, and their Cl – electrosorptive performance in simulated reclaimed water was extensively investigated. The prepared materials were characterised using X-ray diffraction, scanning electron microscopy, N2 adsorption, and Fourier-transform infrared spectroscopy. The experimental results indicated that the optimal Cl – removal rate from the ACF/TiO2 /PANI electrode reached 85.34% when the calcination temperature of TiO2 was 400 °C and the polymerisation concentration of PANI was 0.02 mol·L −1 . This study demonstrated that the ACF/TiO2 /PANI electrode showed an excellent equilibrium adsorption capacity of 17.1 mg·g −1, which was 1.4 times that of the parent ACF. The superior performance was attributed to the modification of TiO2 and PANI, which considerably improved the hydrophilicity, conductivity, and physical adsorption capacity of the electrode. Consequently, the electrosorption rate and adsorption capacity were enhanced. In addition, the prepared ACF/TiO2 /PANI electrode exhibited a high Cl – removal rate of 80.42% (adsorption capacity of 16.88 mg·g −1 ) in actual reclaimed water. Based on these results, the electrosorption kinetics and mechanism of the prepared ACF/TiO2 /PANI electrode were analysed further. Graphical Abstract: ga1 Highlights: A stable ACF/TiO2/PANI composite electrode was constructed with abundant mesopores. The introduction of TiO2 and PANI on ACF electrode enhanced its conductivity, hydrophilicity and adsorption performance. The adsorption process obeyed the pseudo-second order kinetic model, which was also affected by film diffusion and intra-particle diffusion.